P831 Habitual dietary intake of Dutch IBD patients differs from population controls: A case–control study. (16th January 2018) - Peters, V; Tigchelaar, E; Campmans-Kuijpers, M; Sheedfar, F; Imhann, F; Dekens, J; Wijmenga, C; Swertz, M; Franke, L; Weersma, R; Dijkstra, G; Alizadeh, B
Abstract: Background: Dietary habit is essential in the aetiology of inflammatory bowel disease (IBD). However, the question what to eat remains a burden for physicians rather than a solution to patients. We hypothesised that patients follow "unguided" dietary habits after diagnosis of IBD. This dietary behaviour is more of subjective feelings or personal experience rather than being evidence based. We aimed to investigate whether post-diagnosis dietary intake of potential unfavourable and favourable macronutrients and food groups by IBD patients is comparable with those of controls. Methods: Dietary intake of macronutrients and 25 food groups were obtained by means of a validated food frequency questionnaire from 492 patients, consisting of 206 ulcerative colitis and 286 Crohn's disease patients as well as 1297 population-based controls. Based on extensive literature review, food groups were grouped as potentially unfavourable or favourable for IBD. Descriptive analyses and both univariate and multivariate regression models were performed stratified by gender. A p -value <0.0007 was considered statistically significant. Results: Compared with controls (Figures 1 and 2), IBD patients reported lower intakes of several potentially unfavourable dietary factors like alcohol, dairy and prepared meals. Of clinical interest, IBD patients consumed significantly less potentially favourable food groups including bread, cereals, fruits and nuts. Besides, patients consumed significantly more potentially unfavourable foods, including fat, meat, non-alcoholic drinks and sugar/sweets than controls. Conclusions: Our study showed that IBD patients follow "unguided" dietary habits after diagnosis, thereby restricting potentially favourable food groups. This may contribute to potentially unintended effects on disease course and its complications.